Primary : a whole school story. (EBD, 2008)
Allens Croft Primary School has a higher proportion than average of children on the special needs register. 30% for the whole school and 50% in some classes. The secret of managing so many children with complex needs seems to be to prioritise the needs of each child. Supporting individuals above anything else, rather than expecting them to conform to the needs of the school. The school prides itself on this inclusive atmosphere which it achieves by reviewing each child's needs regularly. We concentrate on the extra support given by Heather Cook from the Communication and Autism Team, part of Inclusion Services for Birmingham Education Authority, to two children believed to have autism in Year 2. The programme concentrates on three Year 5 children, two on the autistic spectrum and one who has Attention Deficit Hyperactivity Disorder.